You can't have it all : the basic b*tch guide to taking the pressure off - Schroeder, Stassi (Gallery Books, 2024)
Before she wrote "Off with my head," her memoir about hitting what felt like rock bottom, Stassi Schroeder was working on a book about how to be a "girlboss." But in 2020, after a global pandemic, losing her job, having her first child, and getting married, being a girlboss was no longer the vibe. Instead of giving up, Stassi grew up and learned from her mistakes, and after two and a half years she was ready to relaunch her career with a new perspective on life: to carve her own path, on her own terms. This book is about accepting the fact that you may not be the perfect person at all times, and that's okay. She encourages us all to learn how to take the pressure off, give ourselves grace, and lean into the things that bring us joy.